Differences in presentation and survival of Asians compared to Caucasians with ovarian cancer: An NRG Oncology/GOG Ancillary study of 7914 patients() - Fuh, Katherine C. (Gynecol Oncol, 2019)
PURPOSE. To compare patient/tumor characteristics and outcomes of Asians to Caucasian patients with epithelial ovarian cancer. METHODS. Ancillary data were pooled and analyzed from ten prospective randomized front-line Gynecologic Oncology Group clinical trials from 1996 to 2011. Demographic, clinicopathologic features, disease-specific and all-cause survival were analyzed. RESULTS. Of 7914 patients, 7641 were Caucasian and 273 Asian. When compared to Caucasians, Asians were younger at trial enrollment, had a better performance status, earlier-stage cancers (17.2% vs. 8.1% with stage I; p < 0.001), and were more likely to be of clear cell (15.8% vs. 6.2%, p < 0.001) and mucinous (3.3% vs. 1.9%, p < 0.001) histology. Asians had an improved 5-year disease-specific survival of 54.1% compared to 46.1% for Caucasians, p = 0.001. In multivariate analysis, the Asian race remained a significant prognostic factor for all-cause survival (HR: 0.84; 95% CI: 0.72–0.99; p = 0.04). Other factors predictive of improved survival included younger age, better performance status, optimal cytoreduction, earlier stage, non-clear cell histology, and lower grade tumors. CONCLUSION. Asians enrolled into phase III ovarian cancer clinical trials were younger,with better performance status, earlier-stage of disease, and have a greater number of clear cell andmucinous tumors. After adjusting for these prognostic factors, Asians have a better survival compared to Caucasians.